Tahap kebolehgunaan rekabentuk papan kekunci ergonomik terhadap penggunaan perisian komputer - Sazura, Ramli (Universiti Malaysia Sarawak, (UNIMAS), 2004)
Keyboard is an input and control devices of computer that already through technological and design changes in order to make it more comfortable and safe to use. The question here is how far an ergonomic keyboard can be use in order to achieve easier, faster and safer work management with computer application. For this purpose, this survey is conducted to evaluate level of usability of an ergonomic keyboard towards its usability in computer application base on key arrangement, key control and function, icon and symbol interface. Survey respondent were student of UNIMAS. Data is collected through an observation using task analysis method that has two set of task, and questionnaire also has been used Descriptive statistic has been used in order to display demographic distribution and total of type word per minute achieve by respondent. The overall result show that ergonomic keyboard usability is in optimum level.